Design of Thermostat Controlled Electrical Heating Circuits on Manned Spacecraft. Issue 1 (1st December 2022) - Zhang, Li; Fu, Yang; Tang, Zixin; Chen, Ling; Feng, Maolong
Abstract: A thermostat is a type of contact inductive device. It has the features of being compact, lightweight, and high temperature control precision. A scheme for using a thermostat as a control device in the active electrical heating and temperature control circuit of the spacecraft is proposed. It is in line with the design requirement of the spacecraft thermal control system when the computer controlled heater-system is limited. Compared with the computer-controlled heater system, the thermostat-controlled heater system has the advantages of simple configuration, easy implementation, and high reliability under certain conditions. The thermal design of the shunt regulator, manipulator, portable light, and emergency brake device is analysed given the characteristics of the demands on manned spacecraft. The use of a thermostat to solve the temperature control problem when a computer is not available is a common feature of these thermal designs. The temperature results of the on-orbit test and ground test prove that using a thermostat in the heater system of spacecraft can ensure equipment is within the range of index requirement reliably.